2021
DOI: 10.5152/eurjrheum.2020.20024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anti-citrullinated protein antibody on tumor necrosis factor inhibitor or abatacept response in patients with rheumatoid arthritis

Abstract: The aim of the European Journal of Rheumatology is to cover various aspects of rheumatology for its readers, encompassing the spectrum of diseases with arthritis, musculoskeletal conditions, autoinflammatory diseases, connective tissue disorders, osteoporosis, translational research, the latest therapies and treatment programs. European Journal of Rheumatology publishes original articles, invited reviews, case based reviews, letters to the editor and images in rheumatology. The publication language of the jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…However, short-term follow-up period and low proportions of concomitant use of MTX (59.7–62.4%) and corticosteroid (37.0–38.5%) may affect the outcomes, resulting in a less pronounced improvement of CDAI (− 9.85 for abatacept and − 8.53 for TNFi) compared to our study. The longitudinal CDAI changes reported in another study for abatacept in ACPA-positive patients were similar to our study; −8.53 and −19.01 at 6 and 12 months, respectively [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, short-term follow-up period and low proportions of concomitant use of MTX (59.7–62.4%) and corticosteroid (37.0–38.5%) may affect the outcomes, resulting in a less pronounced improvement of CDAI (− 9.85 for abatacept and − 8.53 for TNFi) compared to our study. The longitudinal CDAI changes reported in another study for abatacept in ACPA-positive patients were similar to our study; −8.53 and −19.01 at 6 and 12 months, respectively [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…At the time of collection of the present data only one Janus kinase (JAK) inhibitor (tofacitinib) [ 29 ] and one IL-6 inhibitor (tocilizumab) [ 30 ] were FDA approved; consequently patients treated with other JAK or IL-6 inhibitors were not included. Additionally, selection bias should be considered as a limitation due to prescribing patterns potentially being influenced by serological status – the impact of serological status in the efficacy of some bDMARDs has gained increasing evidence [ 31 – 34 ]; as such, selection bias may have increased during the study period. As with all real-world studies, patients enrolled in the registry may not fully reflect patients with RA observed in other regions or areas of general practice.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2052 patients were included of which 1415 were in the TNFis cohort ( n = 1053 ACPA positive) and 637 in the Abatacept cohort ( n = 445 ACPA positive). The baseline ACPA score was associated with an improvement in clinical response using a measure of clinical disease-activity index at 12 months for Abatacept therapy, but not for TNFis therapy [ 172 ].…”
Section: Diagnostic and Therapeutic Potential Of Citrullinationmentioning
confidence: 99%